2017
DOI: 10.1177/1046496417710726
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Participation and Social Connections in Online Discussion Forums

Abstract: Social relations are an essential component of group learning online, because through them, the process is managed and controlled. In addition, learning cannot be understood in isolation from its situated nature. To identify patterns of participation and social connections in online group learning, this study analyzes the social network among university students who work in online discussion forums and are required to solve higher order learning tasks. Discussion forums were used, focusing on three types of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…These studies can be placed into two general categories. The first category encompasses studies that have examined how task characteristics and environmental context affect the structure of interaction networks (task complexity and time pressure; Brown & Miller, 2000; learning task complexity; Tirado-Morueta, Maraver-López, & Hernando-Gómez, 2017). Taken together, these studies show that task type exerts a significant influence on team collaboration structures and provided indirect support for the notion that centralized networks are an efficient structure for simple tasks, while dense networks are necessary for the intensive collaboration required of complex tasks (Shaw, 1964).…”
Section: Network Thinking In the Work Teams Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…These studies can be placed into two general categories. The first category encompasses studies that have examined how task characteristics and environmental context affect the structure of interaction networks (task complexity and time pressure; Brown & Miller, 2000; learning task complexity; Tirado-Morueta, Maraver-López, & Hernando-Gómez, 2017). Taken together, these studies show that task type exerts a significant influence on team collaboration structures and provided indirect support for the notion that centralized networks are an efficient structure for simple tasks, while dense networks are necessary for the intensive collaboration required of complex tasks (Shaw, 1964).…”
Section: Network Thinking In the Work Teams Literaturementioning
confidence: 99%
“…The rich longitudinal data required by this approach are typically possible only via unobtrusive data collection approaches. Our review revealed that researchers are gathering this type of data by utilizing archival data collection techniques, including online data trace (e.g., email; Quintane, Pattison, Robins, & Mol, 2013; discussion forum; Tirado-Morueta et al, 2017), archival sports data (e.g., cricket; Mukherjee, 2016; National Basketball Association; Fonti & Maoret, 2016; Major League Baseball; Wang & Cotton, 2018), and online databases (e.g., patent and trademark; Singh & Fleming, 2010; movie database; Cattani & Ferriani, 2008). Moreover, aforementioned new and evolving measurement techniques (e.g., wearable sensors, computer-aided text analysis, and facial recognition technique) may permit more elaborate modeling of team networks than has been feasible in the past (Kozlowski, 2015; Luciano, Mathieu, Park, & Tannenbaum, 2018).…”
Section: Advancing Work Teams Research With Network Thinkingmentioning
confidence: 99%
“…Social network analysis (SNA) is usually used by researchers to improve the understanding of the interactions in online learning and learning communities (e.g., Tirado-Morueta, Maraver-Lo´pez, & Hernando-Go´mez, 2017;Cho, Gay, Davidson, & Ingraeffea, 2007;Dado & Bodemer, 2017;Dawson, Bakharia, & Heathcote, 2010;Jan & Vlachopoulos, 2018;Macfayden & Dawson, 2010). Using SNA, researchers have tried to identify structure of the social network (SSN) that facilitate optimal performance of the group (e.g., Sauer & Kauffeld, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, there are few studies dedicated to analyze the relationships between the SSN and the performance considering the online learning process (e.g., Gunawardena, Lowe, & Anderson, 1997;Wang, Han, Fisher, & Pan, 2017) and the type of task as a moderating variable (e.g., Tirado-Morueta, Maraver-Lo´pez, Hernando-Go´mez, & Harris, 2016;Tirado-Morueta, Maraver-Lo´pez, & Hernando-Go´mez, 2017;Ab Jalil & de Laat, 2014;Mohammed & Harrison, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Formally assessing participation in the discussion board is based on the notion that assessment is a key driver for student learning (Biggs & Tang, 2011;Matheson, Wilkinson, & Gilhooly, 2012). Assessing discussion board participation is somewhat contentious (Osborne, Byrne, Massey, & Johnston, 2018) though much research has found students are more engaged with the course content and gain higher marks (Birch & Volkov, 2007;Maddix, 2012;Song, Rice, & Oh, 2019), display improved critical thinking skills (Brown, 2014;Giacumo & Savenye, 2020), form connections with other students and faculty (Tirado-Morueta, 2017) and apply knowledge to practical situations. assessment of quality in discussion boards did not focus on interaction or engagement.…”
Section: Introductionmentioning
confidence: 99%